EFEKTIVITAS E-LEARNING TERHADAP KEPUASAN MAHASISWA DAN DAMPAKNYA PADA LOYALITAS MAHASISWA DI STMIK PRINGSEWU - Yoeyong Rahsel; Miswan Gumanti (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine whether there is effectiveness of E-learning on student loyalty through student satisfaction at STMIK Pringsewu. The research method used in this research is associative research. In this study the number of respondents taken as many as 120 respondents, with a sampling technique using accidental sampling. The data analysis technique in this study will use Structural Equation Modeling (SEM) while data processing uses smartPLS software. The research shows that the effectiveness of e-learning has a significant impact on student satisfaction, student satisfaction has a significant impact on student loyalty. The effectiveness of e-learning directly does not have a significant impact on loyalty, but the effectiveness of e-learning indirectly has a significant impact on student loyalty through student satisfaction at STMIK Pringsewu Keywords : Effectiveness of e-learning, Student Satisfaction, Student Loyalty, Structural Equation Modeling